Assessment of reliability and maintainability of earth pressure balance tunnel boring machine (EPBTBM) – An approach. (March 2022) - Kumar Agrawal, Anil; Chattopadhyaya, Somnath; Murthy, V.M.S.R.; Kumar Adesh, Adesh
Highlights: EPBTBM are used in soft or mixed ground condition. TBF and TTR data are found independent and identically distributed (IID). MTBF and MTTR were calculated as 11.95 h and 5.78 h respectively. The availability of EPBTBM is about 67%. According to FMECA, disc cutter is the most vulnerable part of the EPBTBM. Abstract: Earth pressure balance tunnel boring machines (EPBTBM) are used in soft or mixed ground conditions often encountered in tunneling operations. The performance of EPBTBM could be enhanced to a great extent by appropriate time management, proper maintenance and reduced unproductive times such as idle hours and breakdown hours using reliability analysis. The reliability of a system primarily depends on time between failure (TBF) and maintainability is based on time to repair (TTR). Investigations on EPBTBM system performance were carried out for an irrigation tunnel through mixed strata conditions and the failure/repair data were collected. TBF and TTR data are found independent and identically distributed (IID). This implies that data are not following any particular trend or correlation. Therefore, these data are fitted in different types of probability distributions such as Gamma, Lognormal, Weibull with Easyfit and MATLAB tools. All the distributions are subjected to a Kolmogorov-Smirnov (k-s) test. Data analysis carried out on EPBTBM deployed in tunnels showed that TBF data and TTR data are found to best fit in General Gamma (4p) and General Gamma distribution respectively. Analysis indicated that ninety percent level of reliability of the system is at 2.64 h of operation whereas the mean time to repair is 5.78 h. The overall availability of the system was 67% which is comparatively less. Failure mode effects and criticality analysis (FMECA) was also carried out to find the critical part of the EPBTBM system. Disc cutter got the highest risk priority number indicating that it is the most vulnerable part of the EPBTBM. This paper reports that the availability of such systems can be increased to 80 percent by appropriate scheduling, preventive maintenance, and effective use of skilled manpower.